If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -1) = -28 Reorder the terms: 4(-1 + 2x) = -28 (-1 * 4 + 2x * 4) = -28 (-4 + 8x) = -28 Solving -4 + 8x = -28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 8x = -28 + 4 Combine like terms: -4 + 4 = 0 0 + 8x = -28 + 4 8x = -28 + 4 Combine like terms: -28 + 4 = -24 8x = -24 Divide each side by '8'. x = -3 Simplifying x = -3
| 4(x-8)=0 | | 22=t | | 8+1.25=16.75 | | 3x+38=16+x | | 184+2h=986 | | x+3x-1+x+15= | | 3x^2-6x+11000=0 | | 4x(x)=49 | | 2x^6*x-95=0 | | 0.2p-10= | | 6-4x=x+7(x+8) | | 144=16t | | 28(p+30)=3,108 | | 8.32+7.76-10.09= | | 3,108=28(p+30) | | x+(3x+4)=112 | | 6(2x-3)=24 | | X+(x-21)=157 | | 2x+12+7x-1=x | | 2(3x+3)=11x+3-5x+3 | | z/(-1)=9 | | -8+x=46 | | X+X-21=157 | | 6.8/(-4)= | | 2x+11x=52+x | | x-(-5)=34 | | 9x+15=5x+1 | | 4*(-4.3)*-2= | | X^2-15x-11000=0 | | 4(x+8)=8x+3-4x+29 | | 4b+3-b=-7+2+b | | 6-3(4x+2)-10x= |